Comparison of Doppler findings and neonatal outcome in fetal growth restriction - B. R., Rekha; A., Pavanaganga; M. P. A., Sai Lakshmi; R., Nagarathnamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Fetal growth restriction (FGR) affects up to 5-10% of pregnancies. It is associated with increased perinatal mortality and morbidity. Doppler studies identify at risk fetuses and help in timing interventions and prognosticate outcomes. The ability of Doppler studies to predict neonatal outcome is studied here. Methods: Prospective study of seventy-two women with singleton pregnancies with gestational age above 28 week and detected to have FGR was done. The patients were subjected to Doppler analysis. Abnormal Doppler indices were compared with neonatal outcomes such as NICU admission, ventilator or CPAP support, sepsis, phototherapy and perinatal mortality. Results: Elevated umbilical artery PI, reduced middle cerebral artery PI and low CP ratio were found in 14, 18 and 36 fetuses. The sensitivity and specificity in predicting neonatal outcome was 25% & 75%, 58.1% and 62% and 17.9% and 75% for umbilical artery PI, MCA PI and CP ratio respectively. None of the Doppler indices showed significant p value. On testing, gestational age at delivery and length of NICU stay, gestational age was a significant determining factor with ‘p’ value of 0.003. Conclusions: Antenatal Doppler analysis of UA and MCA can predict neonatal outcome in FGR fetuses. Though the ‘p’ value was not significant in this study, the sensitivity, specificity, positive predictive value and negative predictive value are comparable to other studies. Gestational age at delivery significantly influences neonatal outcome.